Phenotypic Variation between Monochorionic Diamniotic Twins with Coffin–Siris Syndrome - LaBrecque, Brett; Contreras, Marioxy; Giordano, Jessica; Parravicini, Elvira (Journal of Pediatric Genetics, 2019)
The first known documented case of monochorionic–diamniotic twins with Coffin–Siris syndrome is described in this study. This case is notable because of the phenotypic differences between infants despite having identical genomes and causative variants. Also unique to this case is the clinical influence of early diagnosis using precision medicine techniques.
Keywords: whole-exome sequencing; genetics; neonatology; early diagnosis; precision medicine